Persistent Endodontics Pathogens Biofilm Inhibited by Lactobacillus reuteri Indonesian Strain - Widyarman, Armelia Sari; Lazaroni, Njoo Kiky Elysia (UI Scholars Hub, 2019)
Lactobacillus reuteri is known as probiotics that effective to improve oral health. Objective: To analyze the effect of L. reuteri Indonesian strain, towards Enterococcus faecalis and Candida albicans biofilm growth. Methods: This study was conducted using biofilm assay. Each E. faecalis ATCC-29212 and C. albicans ATCC-10231 were cultured in Brain Heart Infusion Broth, distributed into 96 well-microplate and incubated for 24h, 37°C, anaerobic condition for E. faecalis and aerobic condition for C. albicans. L. reuteri LC382415 (Indonesian strain) was cultured in deMann Rogosa Shar pe Broth and diluted into different concentrations (108,106, and 104CFU/mL) subsequently, each concent ration dist ributed into biofilm well. Biofilm wells without probiotic was used as negative cont rol. Biofilm mass were measured using crystal-violet dye at 490nm using microplate-spectrophotometer. Data was statistically analyzed by one-way ANOVA test, statistical significance set as p<0.05. Results: Significant reduction of biofilm growth of E. faecalis and C. albicans after treatment with L. reuteri. The ideal concentration was found at L. reuteri 108 CFU/mL with 79.2% E. faecalis biofilm reduction and L. reuteri 104CFU/mL with 62.5% C. albicans biofilm reduction compared to control ( p<0.05) set at 100%. The ANOVA test results showed that L. reuteri in all concentrations and all time periods in this study had the ability to inhibit biofilm growth of both species ( p<0.05) compared to negative control. Conclusion: L. reuteri Indonesian strain inhibit the biofilm growth of E. faecalis and C. albicans. This antibiofilm effect may be useful in preventing biofilm growth in root canal.